HEUNINGNESKRANS AND THE STONE AGE SEQUENCE OF THE OHRIGSTAD RIVER CATCHMENT ON THE EASTERN BORDER OF THE GREAT ESCARPMENT, LIMPOPO PROVINCE, SOUTH AFRICA - (:unkn) unknown (My University, 2019)
Heuningneskrans was briefly excavated in 1968 by Peter Beaumont who exposed a 6.35 m deep archaeological sequence. However, as with other sites in the former Transvaal Province, Heuningneskrans has since played a minimal role in subsequent Stone Age research. The site was drawn to our attention while elaborating our research programme at Bushman Rock Shelter (BRS). The sites are approximately 4 km from each other and located in the Ohrigstad Valley, near the Blyde River catchment. This area, on the eastern margin of the Great Escarp-ment, connects the interior plateau of southern Africa (Highveld) with the Lowveld and the Mozambican coastal plain. In 2018, we reopened Heuningneskrans to expose and sample the profiles, contextualise Beaumont's data, evaluate the site's potential, and its complementa-rity with BRS. The excavation exposed a finely stratified sequence illustrating the action of various sedimentary agents. The last use of the site is associated with Iron Age groups, but most of the sequence documents human occupations that predate 27 000 cal. BP, and last until 8000 cal. BP (calibration OxCal 4.3 SHCal 13). The results of this first excavation campaign, together with ongoing investigations at BRS, highlight that this area is instrumental for the study of Middle and Later Stone Age developments in southern Africa.
Keywords: African Research